2020
DOI: 10.1177/1473325020973333
|View full text |Cite
|
Sign up to set email alerts
|

“People look at me like I AM the virus”: Fear, stigma, and discrimination during the COVID-19 pandemic

Abstract: Anti-Asian sentiment is surging because of COVID-19 and there have been incidents of hate crime. This paper presents a reflection by an Asian social work researcher on the impact of this surge on herself and other Asians in America. Reflecting on the history of pandemic, racism against Asian Americans, and anti-Chinese sentiment among other Asian group, the paper provides important points for us to ponder as a community of social workers in the topics of racial justice

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 5 publications
4
22
0
Order By: Relevance
“…Stigma, discrimination and negative emotions like fear, anxiety and helplessness towards persons suffering from infectious disease during a pandemic have been reported in earlier studies (Choi, 2021;Shultz et al, 2015;Bohle, 2013). The current study participants expressed similar fear of seeing the rising number of deaths during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 76%
“…Stigma, discrimination and negative emotions like fear, anxiety and helplessness towards persons suffering from infectious disease during a pandemic have been reported in earlier studies (Choi, 2021;Shultz et al, 2015;Bohle, 2013). The current study participants expressed similar fear of seeing the rising number of deaths during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 76%
“…These findings diverge from those of prior studies ( 11 , 15 ), in which females showed better attitudes toward COVID-19 than men. Perhaps female participants in this study were less likely to report potential symptoms to avoid the stigma of COVID-19, as fear of the stigma associated with COVID-19 is a problem for many people ( 29 , 51 , 52 ).…”
Section: Discussionmentioning
confidence: 90%
“…The adverse financial and public health impact of the COVID-19 pandemic has significantly increased personal economic stress worldwide [ 7 , 27 , 38 , 39 ]. Amid pervasive reports that the virus originated in China, it is alarming that the pandemic has been associated with an escalation of negative and violent reactions towards Asians [ 40 , 41 ]. In both India and the United States, the present findings revealed bias against the Chinese victim on a variety of measures.…”
Section: Discussionmentioning
confidence: 99%